Meaning in Spinoza's method - Garrett, Aaron (Cambridge University Press, 2003)
This original and controversial book examines the geometrical method employed by Spinoza in his masterpiece the Ethics, and suggests that its purpose, in Spinoza's view, was not just to present claims and propositions but also to allow the readers to look at themselves and the world in a different way.